Generalization of the Lambert–Lagrange projection. (2nd April 2016) - Orihuela, Sebastian
Abstract : The Lagrange projection represents conformally the terrestrial globe within a circle. This is achieved by compressing the latitude and longitude and by applying the new coordinates into the equatorial stereographic projection. The same concept can be generalized to any conformal projection, although the application of this technique to other analytical functions is less known. In this work, the general Lambert–Lagrange projection formula is proposed and the application of the modified coordinates is discussed on projections: stereographic, conformal conic and Gauss–Schreiber. In general, the results are merely a curiosity, except for the case of Gauss–Schreiber, where the use of coordinates with altered scale can be applied in the optimization of conformal projections.